Fallen hero among grads to receive scrolls at convocation - Daily Express, (KK) (Daily Express (KK), 2013)
ALOR SETAR: Police officer, ASP Zulkifli Mamat, who was among security members killed in the terrorist intrusion incident in Lahad Datu, was supposed to be among graduates to receive their degree scrolls at the Universiti Utara Malaysia's(UUM) 26th convocation to be held from Nov 30.However, with the unfortunate turn of events, his widow, Noraziah Noor, will be on stage to receive the Bachelor's Degree in Communications on behalf of her late husband.